Anti-Acanthamoeba Activities of Chloroformic Fractions of Trigonella Foenum Graecum (Seed) and Their Cytotoxity on Mice Macrophage Cell - Dodangeh, Samira; Niyyati, Maryam; Kamalinejad, Mohammad (Novelty in Biomedicine, 2015)
Background: Acanthamoeba keratitis (AK) is potentially a sight-threatening infection and its treatment is challenging. This is mainly due to presence of resistant cyst form. Indeed, cysts are highly resistant to current available drugs. Chemical drugs are toxic to human keratocytes. It should also be mentioned that most available anti-Acanthamoeba drugs are poorly cysticidal, In Iran and worldwide, AK cases continue to rise and therefore, novel effective drugs are urgently needed for the treatment of AK. Materials and Methods: In the present study, the in vitro activity of serial dilutions (10, 15, 20 and 25 mg/mL) of chloroformic fractions including primary chloroformic fraction (minimum amount of chloroform), middle chloroformic fraction and remaining chloroformic fraction (most amount of chloroform) of Trigonella foenum graecum seed were evaluated against Acanthamoeba trophozoites and cysts. Cytotoxic assay of fractions at different concentrations (25, 50, 100, 200, 300, 400, 500 mg/ml) of test material was identified on mice Macrophage cells using MTT method. Results: The obtained results revealed that the tested fractions presented anti-amoebic activities in a time and dose dependent cycle. Anti-Acanthamoeba activity of remaining chloroformic fraction was more than other fractions. Trophozoites/cysts were eliminated when incubated with 15 and 20 mg/ml concentrations of remaining chloroformic fraction after 24 hours. Viability of macrophage cells was noted 100 % with 25 and 50 mg/ml concentration of remaining chloroformic fraction. Our results indicate that the plant fractions are safe for mammalian cells. Conclusion: Further studies should be performed in order to detect the active chemical compounds which could be used for the development of novel therapeutic approaches against Acanthamoeba infections. To the best of our knowledge, this is the first study on the activity of chloroformic fractions of Trigonella foenum graecum (seed) against Acanthamoeba spp.